Analisis Faktor-Faktor yang Mempengaruhi Pertumbuhan Kendaraan Listrik di Pulau Jawa sebagai Upaya Pengurangan Emisi Gas Rumah Kaca - Surya Adi Wicaksono; Haryono Setiyo Huboyo; Budi Prasetyo Samadikun (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
In order to reduce the climate change impact due to Greenhouse Gas (GHG) emissions from the transportation sector, many countries such as Indonesia have started to develop policies to promote environmentally friendly transportation technologies. Electric Vehicles are considered a promising sustainable option compared to conventional vehicles, due to advantages such as increased fuel efficiency and reduced exhaust emissions. Objective of this study is to evaluate factors that influence purchase of electric vehicles, while highlighting potential and challenges associated with the purchase. This research uses the Systematic Literature Review (SLR) review method, to collect data from Sciencedirect.com online article database through the Undip SSO (Single Sign On) page. The results of literature review show that the purchase of electric vehicles is influenced by economic factors of the community, infrastructure of electric vehicles, mileage, topography and government subsidies. Results of the analysis based on existing literature with existing conditions in Java Island show that efforts to transition from conventional vehicles into electric vehicles has the potential to reduce GHG emissions. The review results show that there are four main criteria that influence the decision to purchaseelectric vehicles, namely sociodemographic aspects, financial attributes, environmental information and infrastructure conditions